Pemeliharaan Sistem Drainase Sebagai Upaya Menanggulangi Banjir Kelurahan Cisaranten, Kulon Kecamatan Arcamanik, Kota Bandung - Eka Wardhani; Zakariya, Muhamad; Iwan Juwana (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The Arcamanik subdistrict, particularly the Cisaranten Kulon neighborhood, is one of the areas in Bandung City that is prone to flooding due to land use changes and inadequate drainage systems. This study aims to analyze the condition and effectiveness of the drainage system on Cingised Street and provide maintenance recommendations to mitigate flooding. The method for calculating drainage channel dimensions uses SWMM 5.2 software with primary data including direct observation and measurement in the field and secondary data in the form of rainfall and planning documents. The evaluation results on Cingised Street, Cisaranten Kulon Village, Arcamanik Subdistrict, showed a significant discrepancy between the existing channel dimensions and the initial planning, with a difference of 61.04% in the S19-S20 (right) segment and 51.43% in the S15-S16 (left) segment. Sediment accumulation reached a total of 294.9 m3 along the 230-meter channel, which significantly reduced its hydraulic capacity. Modeling using SWMM 5.2 identified 8 segments that experienced overflow, causing flooding and standing water. The recommended solution is periodic sediment dredging and channel dimensioning in inadequate segments to restore flow capacity and minimize the risk of flooding.